Role-Related Participation in Product Design Teams: Individual- and Group-Level Trends. (March 2017) - Bonito, Joseph A.; Keyton, Joann; Ervin, Jennifer N.
Organizations often delegate decision-making tasks to groups and teams. At issue is the extent to which participation during discussion reflects both individual-level characteristics and emergent (i.e., group-level) processes. Drawing upon Hewes's socio-egocentric model and team meeting literature, we used a multilevel approach to examine participation in product-design teams across a series of tasks. Findings indicate that participation consists of both intra- and group-level processes. Team members who were talkative initially continued to participate frequently during the later tasks, and, as predicted, project managers also spoke more often than team members in any other role. In addition, group-level trends became stronger over time, as evidenced by behavioral convergence. Discussion addresses implications for a "middle ground" approach to modeling communicative behavior in groups.